Sensor Placement for Combined Sewer System Monitoring in the Besòs River Basin. Issue 24 (2018) - Cosco, C.; Cugueró, M.À.; Tàsies, F.; Aguiló, P.; Gómez, M.
Abstract: In this paper, a sensor placement methodology for sewer systems monitoring in order to measure direct discharge to the river during intense rainfall events is presented. During these events, Combined Sewer Overflows (CSOs) may occur, causing serious problems of contamination of the corresponding receiving waters. The current national regulation compels sewer systems' managers to monitor and quantify direct discharge to these receiving waters, in order to track these events. Hence, the selection of the appropriate sensor set in order to monitor the critical outlets of the network is of paramount importance to adequately monitor CSOs and minimize their effect by using the information gathered from these measurements. Here, a methodology considering relevant characteristics of each potential monitoring point —e.g. number of discharges, volume discharged or percentage of polluted mass— is defined to select the final sensor set. The presented methodology is applied to three different combined sewer systems in the Besòs river basin nearby Barcelona city area in Catalonia (Spain), i.e. Granollers, La Llagosta and Montornès systems.